2018
DOI: 10.5937/jaes16-17333
|View full text |Cite
|
Sign up to set email alerts
|

Chemical compositional analysis of the Tamarix hispida aerial part extract obtained in ethanol solutions of different concentration

Abstract: In this article, extracts from aerial part of Tamarix hispida Wild harvested in 2016 in the Ile example,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“… Identification Molecular formula Exact mass R t (min) m/z MS/MS fragments Ref. (+ ve) (+ ve) 1 Methyl gallate C 8 H 8 O 5 184.0371 0.64 184.9999 125.9427-141.9137 [ 52 ] 2 Morphinan-4,6-diol, N-formyl-6-acetate(ester) C 19 H 23 NO 4 329.16271 2.31 330.1706 260.1651 [ 53 ] 3 1,6-Di- O -galloyl- d -glucose (nilocitin) C 20 H 20 O 14 484.0853 2.42 485.0025 171.0516-315.0885- 333.0927 [ 30 , 54 ] 4 Hispidulin C 16 H 12 O 6 300.06339 7.08 300.9978 287.0618, 271.0781 [ 55 ] 5 Methyl gallate methyl ether C 9 H 10 O 5 198.05282 7.53 199.0607 183.2035, 182.1017, 168.1108, 167.1539 [ …”
Section: Resultsmentioning
confidence: 99%
“… Identification Molecular formula Exact mass R t (min) m/z MS/MS fragments Ref. (+ ve) (+ ve) 1 Methyl gallate C 8 H 8 O 5 184.0371 0.64 184.9999 125.9427-141.9137 [ 52 ] 2 Morphinan-4,6-diol, N-formyl-6-acetate(ester) C 19 H 23 NO 4 329.16271 2.31 330.1706 260.1651 [ 53 ] 3 1,6-Di- O -galloyl- d -glucose (nilocitin) C 20 H 20 O 14 484.0853 2.42 485.0025 171.0516-315.0885- 333.0927 [ 30 , 54 ] 4 Hispidulin C 16 H 12 O 6 300.06339 7.08 300.9978 287.0618, 271.0781 [ 55 ] 5 Methyl gallate methyl ether C 9 H 10 O 5 198.05282 7.53 199.0607 183.2035, 182.1017, 168.1108, 167.1539 [ …”
Section: Resultsmentioning
confidence: 99%
“…This plant contains biologically active substances polyphenols, terpenoids, and a complex of steroids. It has been proven that extracts and individual components have antimicrobial, antifungal, antiamnestics, cytotoxic, and antioxidant properties and are active as hemostatic agents, as well as against diabetes mellitus [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In different papers [15][16][17][18], it was found that the Tamarix hispida plant has high antioxidant properties in vitro due to the presence of terpenoid compounds in its composition [8]. In addition, the qualitative and quantitative component composition of the Tamarix hispida plant has been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation